Abiotic dissolution and biological uptake of nitrous oxide in Mediterranean woodland and pasture soil. (March 2015) - Warneke, Soeren; Macdonald, Bennett C.T.; Macdonald, Lynne M.; Sanderman, Jonathan; Farrell, Mark
Abstract: Soil is generally regarded as a net emitter of nitrous oxide (N2 O). However, there are numerous field studies showing net uptake of N2 O from soil in different ecosystems. Consumption of N2 O may be abiotic (absorption by water; adsorption by soil matrix) and biotic (microbial reduction of N2 O). This study is the first using undisturbed soil cores to determine the capacity of soil to consume N2 O and discuss the fate of N2 O. We exposed the base of undisturbed soil cores from Mediterranean pasture and woodland soil to elevated concentrations of N2 O and sulphur hexafluoride (SF6 ; as tracer gas). Headspace concentrations of N2 O and SF6 were determined over time and consumption rates of N2 O were calculated ranging from 148.8 ± 19.8 ng N2 O min −1  g −1 to 163.8 ± 17.2 ng N2 O min −1  g −1 in woodland soil and from 117.2 ± 36.1 ng N2 O min −1  g −1 to 145.1 ± 19.4 ng N2 O min −1  g −1 in pasture soil. Absorption of N2 O by soil water contributed 17–49% of the total N2 O consumption. The remaining N2 O consumed by the cores was due to adsorbtion by the soil matrix and/or reduction by microbes. Mediterranean soil from different ecosystems with different nitrogen (N) loads has a great potential to store and consume N2 O, if exposed to an N2 O elevated atmosphere. Highlights: N2 O consumption measured from soil cores using SF6 to simulate inert N2 O diffusion through the soil. Mediterranean woodland and pasture soils consumed from 117.2 ± 36.1 to 163.8 ± 17.2 ng N2 O min −1  g −1 . Abiotic absorption of N2 O by soil water of the cores ranged from 17% to 49% of the total N2 O consumed.